Essays in honor of M. Hashem Pesaran : panel modeling, micro applications, and econometric methodology - Chudik, Alexander; Hsiao, Cheng; Timmermann, Allan (Bingley, U.K. : Emerald Publishing Limited, 2022)
The collection of chapters in Volume 43 Part B of Advances in Econometrics serves as a tribute to Professor M. Hashem Pesaran. Hashem is one of the most innovative, influential, and productive econometricians of his generation, with over 200 papers published in leading scientific journals to his credit along with highly influential books on both theoretical and applied topics, significantly pushing forward the frontiers of knowledge in econometrics and economics. Thanks to his profound and pioneering work on theoretical and empirical questions, the economics profession has gained a much better understanding of both the power and limitations of econometric analysis. Reflecting the diversity of Hashem's many contributions, this volume includes chapters on a wide variety of topics, including panel modelling, micro applications, and econometric methodology. The long list of topics includes studies analysing multiple treatment effects in panels, heterogeneity and aggregation, an exploration of the Orthogonal to Backwards Means (OBM) estimator, and an examination of potential reasons for anaemic productivity growth in Italy using recent dynamic heterogeneous panel data methods developed by Hashem Pesaran and his co-authors.
Introduction / Alexander Chudik, Cheng Hsiao, and Allan Timmermann -- Part b1. Panel data methods -- Chapter 1. A panel data model with generalized higher-order network effects / Badi H. Baltagi, Sophia Ding, and Peter H. Egger -- Chapter 2. Spatial and spatio-temporal granger representation, networks and common correlated effects / Arnab Bhattacharjee, Jan Ditzen, and Sean Holly -- Chapter 3. Heterogeneity and dynamic dependence in panel analysis of individual behaviour / Kannika Damrongplasit and Cheng Hsiao -- Chapter 4. Multiple treatment effects in panel-heterogeneity and aggregation / Cheng Hsiao, Yan Shen, and Qiankun Zhou -- Chapter 5. Backward mean transformation in panel data with predetermined regressors / Arturas Juodis -- Chapter 6. Various asymptotic distributions of the error-components test for cross-sectional correlation / CY Sin -- Chapter 7. Trimmed mean group estimation / Yoonseok Lee and Donggyu Sul -- Part b2. Micro modeling -- Chapter 8. Corporate indebtedness and low productivity growth of Italian firms / Gareth Anderson and Mehdi Raissi -- Chapter 9. Women's potential earnings distributions / Esfandiar Maasoumi and Le Wang -- Part b3. Econometric methodologies -- Chapter 10. Where (and by how much) does a theory break down? With an application to the expectation hypothesis / Karim M. Abadir and Christina Atanasova -- Chapter 11. Gaussian rank correlation and regression / Dante Amengual, Enrique Sentana, Zhanyuan Tian -- Chapter 12. Robust dynamic panel data models using e-contamination / Badi H. Baltagia, Georges Bresson, Anoop Chaturvedi, and Guy Lacroix -- Chapter 13. Identification-robust inference for endogeneity parameters in models with an incomplete reduced form / Jean-Marie Dufour and Vinh Nguyen.
Includes index.
Includes bibliographical references.
Keywords: Econometrics; Business & Economics -- Econometrics; Econometrics